Lymphogranuloma Venereum-Associated Proctitis Mimicking a Malignant Rectal Neoplasia: Searching for Diagnosis - Pimentel, Raquel (2022)
Background: Chlamydia trachomatis-lymphogranuloma venereum (LGV) is a sexually transmitted infection (STI) and an uncommon cause of proctitis. The diagnosis requires a high index of clinical suspicion, since the clinical, imaging, endoscopic, and histological findings can mimic multiple benign or malignant conditions like inflammatory bowel disease and rectal neoplasms. Case Presentation: We present the case of a 48-year-old Caucasian male with no significant previous medical history who was admitted due to the suspicion of a rectal neoplasia. He underwent an abdominopelvic computed tomography (CT) scan and pelvic magnetic resonance imaging (MRI) before admission due to complaints of anorectal pain, hematochezia, and constipation over the previous 2 weeks. The examination revealed a circumferential rectal wall thickening, infiltration of the perirectal fat and invasion of the mesorectal fascia, associated with perirectal fat lymphadenopathy. A radiological diagnosis of a rectal malignant neoplasia staged as T4N2MX was stated. Digital rectal examination identified a circumferential rectal tumor. Rectosigmoidoscopy showed an extensive and circumferential ulceration of the rectal mucosa, with elevated geographical borders, exudate, and aphthoid erosions at the proximal limit of the endoscopic mucosal ulceration. Biopsy specimens revealed acute ulcerative proctitis with lymphoplasmocytic inflammatory infiltrate but no evidence of dysplasia or malignancy. A STI screening was positive for HIV-1 (CD4+ 251/mm3; N = 700–1,100) and C. trachomatis, with an elevated IgA-specific antibody titer (52.000; N < 5.0), suggesting LGV disease. The diagnosis was confirmed by the identification of C. trachomatis DNA on rectal swab. Other infectious causes of acute proctitis were excluded. When faced with these results, the patient ended up mentioning that he had unprotected anal sex with men. He started treatment with doxycycline 100 mg twice a day for 21 days, with a drastic improvement. Rectosigmoidoscopy was repeated and showed clear signs of progressive resolution of the ulcerative proctitis. Discussion: LGV-associated proctitis, often undervalued, is a reemerging disease which should always be considered a benign cause of rectal mass, in order to avoid delay in diagnosis and development of complications. Diagnosis becomes more challenging in patients with unknown HIV status. A detailed clinical history, including sexual behaviors, is a vital step to achieve the final diagnosis.